Position Control of an Object Coupled with Motor via Elastic Joint - Geleževičius, V. A. (Elektronika ir Elektrotechnika, 2009)
The control method enabling compensating of influence of certain mismatch between estimated and real parameters of elastic coupling and transported object on dynamical quality of positioning is presented and investigated. An additional speed regulation contour ensuring object speed compensation in accordance of signal generated by reference model is applied for this purpose. The two types of speed correction controllers are investigated. The system modeling results are presented. Ill. 7, bibl. 3 (in English; summaries in English, Russian and Lithuanian).